Inhibition of Vascular Endothelial Growth Factor Receptor 3 Reduces Migration of Gastric Cancer Cells. (14th September 2015) - Lim, Jaeyoung; Ryu, Ji Hyeon; Kim, Eun-Jin; Ham, Songhee; Kang, Dawon
Abstract : Angiogenesis induced by proangiogenic molecules such as vascular endothelial growth factor (VEGF) is a key process in the progression and metastasis of gastric cancer. In this study, we investigated the role of VEGF-C/VEGF receptor 3 (VEGFR3) axis in cell proliferation and migration/invasion of human gastric cancer cells (hGCCs). VEGF-C did not enhance cell proliferation but increased cell migration/invasion by approximately ∼50% in hGCCs (AGS and SNU-484). MAZ51, a VEGFR3 inhibitor, reduced the VEGF-C-induced increase in migration/invasion by ∼30% ( p < 0.05). These results suggest that VEGFR3 could be a therapeutic target for reducing the metastasis of gastric cancer cells.